2009
DOI: 10.1590/s1413-41522009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do processo de fluoretação nos sistemas de abastecimento de água da região de Araçatuba, São Paulo

Abstract: Resumo AbstractThis paper focuses on the drinking-water fluoridation process in Araçatuba region water supply systems by means of 5.157 fluoride concentration data from 2001 to 2005. These data were studied based on the water source, the administration and the structure of the water supply system, according to the population of the county and the type of management. Almost half of samples did not comply the fluoridation standard and the higher compliance was verified in the water supply systems operated by Sab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
1
5
0
3
Order By: Relevance
“…The average fluoride content of 0.50 mg F/L (Figure 2b) in the present study is close to the mean of 0.55 mg F/L found by Peixoto et al 16 , who evaluated fluoride concentrations in the water supply of the municipality of Juguaribara, Ceará, and the mean of 0.57 mg F/L found in research performed with 5,157 water samples from the municipality of Araçatuba, São Paulo, by Daré et al 34 . Ramires et al 13 , analyzed 737 water samples from throughout the population of the city of Bauru, São Paulo, and found monthly mean fluoride concentrations to vary between 0.37 and 1.00 mg F/L, with about 85% of the sample means being between 0.55 and 0.84 mg F/L, and an average value of 0.75 mg F/L.…”
Section: General Analysissupporting
confidence: 92%
“…The average fluoride content of 0.50 mg F/L (Figure 2b) in the present study is close to the mean of 0.55 mg F/L found by Peixoto et al 16 , who evaluated fluoride concentrations in the water supply of the municipality of Juguaribara, Ceará, and the mean of 0.57 mg F/L found in research performed with 5,157 water samples from the municipality of Araçatuba, São Paulo, by Daré et al 34 . Ramires et al 13 , analyzed 737 water samples from throughout the population of the city of Bauru, São Paulo, and found monthly mean fluoride concentrations to vary between 0.37 and 1.00 mg F/L, with about 85% of the sample means being between 0.55 and 0.84 mg F/L, and an average value of 0.75 mg F/L.…”
Section: General Analysissupporting
confidence: 92%
“…These data suggest that is more difficult control the fluoridation from AWs than WTPs, in agreement with the data from other studies conducted in Capão Bonito 27 and Araçatuba, SP. 28 However, in terms of the risk of fluorosis, the findings showed that only one sample from one month was within the range of high risk of fluorosis for water from AWs (14% in September) and from the WTP (5% in March). Regarding caries, only one sample from one month would have subjected the population to insignificant anticaries benefit (14% in September) and then only for samples originating from AWs.…”
Section: Discussionmentioning
confidence: 94%
“…Em relação à distribuição espacial das amostras no território, a descrição na maioria dos estudos foi bastante sucinta indicando apenas o número de pontos de coleta (Tabelas 1 e 2). A justificativa geral mencionada foi buscar representar todo o sistema de distribuição (Daré et al 2009). Entre os estudos que descreveram critérios para a distribuição espacial das amostras, pode-se distinguir aqueles que definiram o número de pontos de coleta conforme o porte populacional (D'Alessandro et al, 2008;Catani et al, 2008;Panizzi e Peres, 2008); e aqueles que definiram os pontos segundo o número de unidades de tratamento ou fontes de abastecimento (Saliba et al, 2009;Silva et al, 2009;Olivati et al, 2011;Moimaz et al 2012a;2012b;2012c).…”
Section: Resultsunclassified
“…Entre os possíveis fatores associados levantados pelos estudos destacaram-se: padrão geológico do solo (Silva et al, 2009;Sampaio et al, 2010;D'Alessandro et al, 2008;Akpata et al, 2009;Viswanathan, 2009;Wambu et al, 2011;Lupo et al, 2012); áreas rurais em comparação com urbanas (Yarmolinsky et al, 2009;Olivati et al, 2011); tipo de manancial, porte do sistema, concessionária, o nível de desenvolvimento humano municipal (Daré et al, 2009); tipo de sistema de abastecimento: estação de tratamento; estação de tratamento e poço tubular profundo; poço tubular profundo (Silva et al, 2011); abastecimento por sistemas de poços artesianos, o que dificultaria, sobremaneira, o controle operacional do método (Bellé et al, 2009); problemas no equipamento hidráulico ou em variações no fluxo de água (vazão) ao longo da rede de distribuição da cidade, velocidade de esvaziamento dos reservatórios distribuídos que não estão interligados entre si (Marmolejo e Coutinho, 2010); dificuldades operacionais e interpretação da legislação (Panizzi e Peres, 2008;Moraes et al, 2009;Saliba et al, 2009); o tipo de técnica analítica (Motter et al, 2011). Aventou-se ainda a presença natural de fluoreto nas águas de alguns municípios (Scorsafava et al, 2011) e sugeriu-se que quanto menor o número de fontes de água no município, melhor o controle (Moimaz et al, 2012b).…”
Section: Resultsunclassified